One health approach on zoonotic helicobacter pylori in animals and man - Eissa, Nourhan; Mohamed, Maha A; Shahban, Rahma S; Badrkhan, Salma M; Mohamed, Jana F; Elsayed, Somaya A; Harb, Ola H (Animal Review, 2024)
Zoonotic disease-causing microbes are those naturally spread from animals to people, either directly or indirectly, with a serious hazard on the public health. Emerging zoonoses are mostly caused by travel, animal transhumance, population increase, and migration from rural to urban regions. Regarding the principal transmission route of Helicobacter pylori (H. pylori), one of the most global prevalent anthroponotic illnesses, not a lot of information is currently known. In the 20th century, H. pylori contribute to individuals stomach problems and cancer. Subsequently, an extensive amount of study has been conducted on the epidemiology of this intestinal infection, revealing that the likelihood of illness varies throughout individuals. This is a concise overview of the several epidemiological factors connected to zoonotic H. pylori infection. There are notable differences in the epidemiology of H. pylori in human and animal populations between developing and developed nations. Moreover, a multiplicity of consistent lines of evidence suggests that demographic data, different individual habits, socioeconomic position and living conditions are the main risk factors influencing the acquisition rate of H. pylori pathogen. These results are troubling since they are expected to change global demography and increase the number of people susceptible to H. pylori and its emergence. To reduce the danger to public health and the associated economic effects, stakeholders in the H. pylori management plan need to start merging technological, social, political, policy, and regulatory problems and working together. An active mitigation program offers the chance to address global health concerns and halt the development of zoonoses.